Depressive symptoms are not associated with long-term integrated testosterone concentrations in hair. (21st April 2021) - Walther, A.; Wehrli, S.; Kische, H.; Penz, M.; Wekenborg, M.; Gao, W.; Rothe, N.; Beesdo-Baum, K.; Kirschbaum, C.
Abstract: Objectives: The association between depressive symptomatology and endogenous testosterone levels is inconclusive. Large inter- and intra-individual testosterone differences suggest point measurements from saliva or serum to be inadequate to map basal testosterone concentrations highlighting the potential for long-term integrated testosterone levels from hair. Methods: Using data from a prospective cohort study, a total of 578 participants (74% female) provided complete data on depressive symptomatology, clinical features, and hair samples for quantification of testosterone concentrations at baseline. Available data of three annual follow-up examinations were used for longitudinal analyses. Results: Correlation analysis showed in both, men and women, hair testosterone across all the four time points not to be significantly related to depressive symptoms. Examined clinical features were not associated with testosterone levels, except for having a current diagnosis of a psychological disorder, which was associated with reduced testosterone levels in men, but not in women. Acceptable model fit for an autoregressive cross-lagged panel analysis emerged only for the female subsample suggesting inverse cross-relations for the prediction of testosterone by depressive symptomatology and vice versa. Conclusions: Findings from this study add to the literature by showing no association between long-term integrated testosterone in hair and depressive symptomatology in men and women.